The Effect Of ROA, ROE, NPM And Company Age On Income Smoothing - Setyo Prastiwi; Adia Adi Prabowo (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to examine the effect of return on assets, return on equity, net profit margin and company age on income smoothing. The sample in this study were manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in 2015-2019, based on the purposive sampling method obtained 49 companies. In this study the data were processed using SPSS with multiple linear regression. The method of testing the hypothesis uses a significance level of 5%. The result showed the return on assets variable had no effect on income smoothing. Return on equity has no effect on income smoothing. Net profit margin has a negative effect on income smoothing. Company age has no effect on income smoothing.